Covenant - Michener, James A. (Random House, 1980)
By mrliteral October 29, 2003 Sometimes it's nice to read a small book, a quick 150-300 page diversion from the real world. At other times, however, it's nice to read a book with some real "meat" to it. Few big name writers were more adept at producing these meaty books than James Michener, and in the Covenant, he presents one of his biggest, a 1200+ page epic about South Africa. As usual, Michener is not as interested in adventure or characters as he is with relating the history of a particular region. This is his formula: to cover a region from prehistoric times to the present, watching it slowly get settled and eventually civilized, though this civilization is often with a great price. This is not to say that he doesn't write a compelling story: he does, but he does not use heroes or villains to populate his world. This is a good book, but a reader new to Michener should learn to try and not get too attached to specific characters, as Michener treats them rather unsentimentally, and they often die in undramatic fashion. Also, although there are some unpleasant people, Michener does not make them truly evil; he usually can show that these characters believe they have justifiable reasons for their actions. Writing as objectively as possible in a novel, he judges no one but rather allows the reader to make the judgements. Many will be put off by the size of this book, but this is actually a reasonably fast read. In the end, the reader will feel both entertained and educated, and that is perhaps the best that can be asked of from a novel.